Impact of Glycemic Variability and Hypoglycemia on the Mortality and Length of Hospital Stay among Elderly Patients in Brazil - Bruginski, Danielle; Précoma, Dalton B.; Sabbag, Ary; Olandowski, Marcia (Current Diabetes Reviews, 2020)
Background: Glycemic variability (GV) is an alternative diabetes-related parameter that has been associated with mortality and longer hospitalization periods. There is no ideal method for calculating GV. In this study, we used standard deviation and coefficient of variation due to their suitability for this sample and ease of use in daily clinical practice. Objective: This study aimed to investigate the association between GV, hypoglycemia, and the 90-day mortality and length of hospital stay (LOS) among non-critically ill hospitalized elderly patients. Methods: The medical records of 2,237 elderly patients admitted to the Zilda Arns Elderly Hospital over a 2.5-year period were reviewed. Hypoglycemia was defined as a glucose level <70 mg/dL (hypoglycemia alert value) and represented by the proportion of days in which the patient presented with this condition relative to the LOS. The Charlson comorbidity index was used to evaluate prognosis. Data were analyzed using multiple linear and logistic multivariate regression analyses. Results: Adjusted analysis of 687 patients (305 men [44.4%] and 382 women [55.6%], mean age of 77.86±9.25 years) revealed that GV was associated with a longer LOS (p=0.048). Mortality was associated with hypoglycemia (p=0.005) and mean patient-day blood glucose level (p=0.036). Variables such as age (p<0.001), Charlson score (p<0.001), enteral diet (p<0.001), and corticosteroid use (p=0.007) were also independently associated with 90-day mortality. Conclusion: Increased GV during hospitalization is independently associated with a longer LOS and hypoglycemia in non-critically ill elderly patients, while the mean patient-day blood glucose is associated with increased mortality.
Keywords: hospital stay